ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN EMISI GAS RUMAH KACA PADA PERUSAHAAN DI INDONESIA - Rizqi Abdul Majid; Imam Ghozali (Diponegoro Journal of Accounting, 2015)
This research aims to obtain empirical evidence about factors influencing the extent of voluntary greenhouse gas emission disclosure on Firms operate in Indonesia. The independent variables in this research are PROPER ranking, firm size, profitability, leverage, and media. Research population are companies listed on Indonesian Stock Exchange for the year 2011-2013. Sixty nine companies become the final sample of this research.The result of multivariate regression analysis shows that firm size, profitability, and media exposure have positive and significant effect on the extent of greenhouse gas emission disclosure. In contrast, leverage negatively and significantly affects the extent of disclosure. The result of analysis also shows that there is no significant effect of PROPER ranking on the extent of greenhouse gas emission disclosure.